2020
DOI: 10.1039/d0cp05782g
|View full text |Cite
|
Sign up to set email alerts
|

Conformer-specific VUV-MATI spectroscopy of methyl vinyl ketone: stabilities and cationic structures of the s-trans and s-cis conformers

Abstract: Methyl vinyl ketone (MVK), a volatile compound with photochemical activity, has received considerable attention in the fields of environmental chemistry and atmospheric chemistry. We explored the conformational stabilities of MVK...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…In addition, the 0-0 band positions for the s-cis conformers in the two isomers corroborated the AIE values determined in previous studies. 9,10 The assignments of the peaks observed in the IR hole-burn spectra of the individual conformers in the two isomers are listed in Table 2 alongside the calculated results and previously reported values. Owing to the vibrational excitations for the s-cis conformers of MVK and CA in the S 0 state, the 0-0 band signals were depleted by 4.3% and 20.9%, respectively.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In addition, the 0-0 band positions for the s-cis conformers in the two isomers corroborated the AIE values determined in previous studies. 9,10 The assignments of the peaks observed in the IR hole-burn spectra of the individual conformers in the two isomers are listed in Table 2 alongside the calculated results and previously reported values. Owing to the vibrational excitations for the s-cis conformers of MVK and CA in the S 0 state, the 0-0 band signals were depleted by 4.3% and 20.9%, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…[1][2][3][4] Such techniques reduce conformational complexity by utilizing the adiabatic cooling of molecules that results from supersonic expansion in the absence of the non-equilibrium kinetic effect. 5,6 Subsequent investigations have revealed that molecules with a sufficiently low conformer interconversion barrier exist in conformational equilibrium even at low temperatures, [7][8][9] whereas conformers with a high interconversion barrier retain their original composition during cooling via supersonic expansion. [10][11][12] For the former case, identifying peaks that correspond to a specic conformer in measured vibrational spectra requires additional exploration of the vibrational temperature-dependent conformational population, which, in turn, depends on the constructed potential energy surfaces associated with conformational interconversion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[31] Other studies showed that relative energies between two torsional conformations of methyl vinyl ketone cation predicted using popular B3LYP [17] or CAM-B3LYP [32] functionals do not match experiment. [33] MAE, S b In this study, we explain the source of the DFT torsional barrier error and propose a simple method to improve various carbon-carbon torsional barriers, including long polymers. First, we create a carbon torsional barrier (CTB) dataset consisting of 279 torsional barriers with various functional groups attached to carbon atoms.…”
mentioning
confidence: 99%